2019
DOI: 10.1007/s10340-019-01115-7
|View full text |Cite
|
Sign up to set email alerts
|

Crowd surveillance: estimating citizen science reporting probabilities for insects of biosecurity concern

Abstract: Data streams arising from citizen reporting activities continue to grow, yet the information content within these streams remains unclear, and methods for addressing the inherent reporting biases little developed. Here, we quantify the major influence of physical insect features (colour, size, morphology, pattern) on the propensity of citizens to upload photographic sightings to online portals, and hence to contribute to biosecurity surveillance. After correcting for species availability, we show that physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 14 publications
1
33
1
Order By: Relevance
“…brassicae eggs and larvae occurred on low growing, readily accessible host plants and larval feeding damage became more conspicuous as defoliation proceeded. These attributes increased the practicality and efficacy of manual searches, and would also have helped to foster public reports of sightings [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…brassicae eggs and larvae occurred on low growing, readily accessible host plants and larval feeding damage became more conspicuous as defoliation proceeded. These attributes increased the practicality and efficacy of manual searches, and would also have helped to foster public reports of sightings [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…To take another example of a type of increasingly widely used messy data, posts on social media platforms such as Twitter can be searched to provide early warnings of biosecurity risks such as agricultural pests; 38 the costs required to conduct such surveillance with professional observers would be vastly higher and might not necessarily lead to better information. Social media can also illuminate clandestine human behaviors such as illegal wildlife trading (IWT) when the pertinent question is whether this trading is happening, as well as general information on its characteristics rather than detailed questions on trends and absolute magnitudes.…”
Section: Figure 1 Graphical Illustration Of Messy Datamentioning
confidence: 99%
“…The continued expansion of passive surveillance schemes in plant health (Pocock et al 2017a ; Brown et al 2017a ; Baker et al 2018 ; Meentemeyer et al 2015 ; Ryan et al 2018 ; Caley et al 2019 ; Rallapalli et al 2015 ) presents an opportunity for a step change in availability of surveillance data and pest detection capabilities. However, data from passive surveillance are generally “messy” (Dobson et al 2020 ) or “noisy” (Isaac and Pocock 2015 ) and can be difficult to understand.…”
Section: Understanding and Interpreting Data From Passive Surveillancmentioning
confidence: 99%
“…Moreover, detection probabilities will not only differ depending on the individual recorder, but also on the species of concern. Caley et al ( 2019 ) found that the physical features of insect species had a strong effect on detection and reporting probability, and thus that larger more colourful pests such as Monochamus spp. (e.g.…”
Section: Understanding and Interpreting Data From Passive Surveillancmentioning
confidence: 99%